Characterization of Arsenic Biotransformation Products from an Open Anaerobic Degradation of Fucus distichus by Hydride Generation Gas Chromatography Atomic Absorption Spectrometry and High Performance Liquid Chromatography Inductively Coupled Plasma Mass Spectrometry. (2nd November 2013) - Ojo, Abiodun A.; Onasanya, Amos
Abstract : This work reports on the isolation and determination of biotransformation products obtained from the organoarsenic compounds that are present in Fucus distichus when it was subjected to an open anaerobic decomposition by using the Hydride Generation Gas Chromatography Atomic Absorption Spectrometry (HG-GC-AAS) and High Performance Liquid Chromatography Inductively Coupled Plasma Mass Spectrometry (HPLC-ICP-MS). The seaweed and filtrate residues obtained from the open anaerobic degradation procedure were extracted in methanol and partitioned in phenol-ether-water mixtures to obtain water soluble extracts. The water soluble extracts were cleaned up and separated on a gel permeation Sephadex G15 column. Arsenic species concentrations were determined by using HG-GC-AAS. Final characterization of the biotransformation isolates was carried out on HPLC-ICP-MS. Only two arsenic species, 2-dimethylarsinoyl ethanol (DMAE) and dimethylarsinic acid (DMAA), were positively identified in the water soluble extract of the marine brown algae. The two arsenic species are strong intermediate candidates in the biosynthesis of arsenobetaine from oceanic arsenate in marine food webs.